2014
DOI: 10.1007/s10940-014-9221-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Consistency in Sentencing: Exploring the Effects of Guidelines in England and Wales

Abstract: Objectives: The development and application of methods to assess consistency in sentencing before and after the 2011 England and Wales assault guideline came into force.Methods: We use the Crown Court Sentencing Survey to compare the goodness of fit of two regression analyses of sentence length on a set of legal factors before and after the assault guideline came into force. We then monitor the dispersion of residuals from these regressions models across time. Finally, we compare the variance in sentence lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The preferred quantitative approach to studying inter-court disparities is currently a multi-level modelling approach (Merrall et al, 2010; Pina-Sánchez and Linacre, 2016). This has recently been used in several studies measuring inter-judge and inter-court disparities (Fearn, 2005; Johnson, 2006; Merrall et al, 2010; Pina-Sánchez and Linacre, 2013, 2014; Roberts and Pina-Sánchez, 2015). Although this method has many advantages, its one disadvantage is that it does not enable direct comparisons across jurisdictions (Merrall et al, 2010; Pina-Sánchez and Linacre, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferred quantitative approach to studying inter-court disparities is currently a multi-level modelling approach (Merrall et al, 2010; Pina-Sánchez and Linacre, 2016). This has recently been used in several studies measuring inter-judge and inter-court disparities (Fearn, 2005; Johnson, 2006; Merrall et al, 2010; Pina-Sánchez and Linacre, 2013, 2014; Roberts and Pina-Sánchez, 2015). Although this method has many advantages, its one disadvantage is that it does not enable direct comparisons across jurisdictions (Merrall et al, 2010; Pina-Sánchez and Linacre, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The third approach investigates whether disparity arises from different assessments of the numerous legal factors that influence the sentence. Examples of such factors are previous convictions (Roberts and Pina-Sánchez, 2015; Roberts and Von Hirsch, 2010), sentencing for multiple offences (Vibla, 2015) and aggravating or mitigating factors (Pina-Sánchez and Linacre, 2014; Roberts, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent evidence from England and Wales suggests that sentencers might indeed be following the processes outlined in the guidelines. For example, Pina-Sánchez (2015) and Pina-Sánchez and Linacre (2014) found that sentencing consistency increased following a reformatting of the guidelines which explicitly sought to achieve this goal. The new format provides a much longer and clearer list of aggravating and mitigating factors than its predecessor, corresponding with findings by Roberts et al (2018) that sentencers reported taking more factors into account after this change was introduced.…”
Section: Sentencing Guidelines As Choice Architecturementioning
confidence: 99%
“…However, until recently, the almost complete absence of empirical assessments of these new guidelines cast doubts over what, if any, changes in sentencing practice had resulted from their introduction (Ashworth, 2013; Ashworth and Roberts, 2013; Padfield, 2013). The release of the Crown Court Sentencing Survey – a government dataset describing cases processed in the Crown Court – has reversed this trend, transforming the landscape from one dominated by theoretical commentaries to one that is more evidence based (see, for example, Belton, 2018; Fleetwood et al, 2015; Irwin-Rogers and Perry, 2015; Lightowlers, 2018; Lightowlers and Pina-Sánchez, 2017; Maslen, 2015; Maslen and Roberts, 2013; Pina-Sánchez, 2015; Pina-Sánchez and Grech, 2018; Pina-Sánchez and Linacre, 2013, 2014; Pina-Sánchez et al, 2016; Roberts, 2013a; Roberts and Bradford, 2015; Roberts and Pina-Sánchez, 2014; Roberts et al, 2018).…”
Section: Consistency Of Approach Through a Sequence Of Stepsmentioning
confidence: 99%
“…Most of the above cited studies have relied on regression modelling techniques to explore topics such as compliance with the guidelines, consistency in sentencing or the specific effect of certain guideline factors. For example, Pina-Sánchez and Linacre (2013) look at custodial sentence length for offences of assault, refuting the widely held proposition that there are extensive unwarranted disparities in sentencing between courts, while Pina-Sánchez and Linacre (2014) demonstrated that the application of the new assault guideline has led to an increase in consistency. Roberts and Bradford (2015) showed that there are aggravating and mitigating factors having an undue influence on the guilty plea discount, which raises questions about compliance with the guidelines.…”
Section: Consistency Of Approach Through a Sequence Of Stepsmentioning
confidence: 99%